Analisis Manajerial Kepala Sekolah dan Kinerja Guru Terhadap Kemandirian Belajar Siswa Masa Pandemi Covid-19 - Ratna Irawati; Dita Riyanto Putro (Universitas Islam Kadiri, 2023)
The managerial ability of the principal is very necessary in the learning process among planning, organizing, driving, and supervising. That ability is to prepare teachers in carrying out a better learning performance process. In addition, that ability is also to find out and explore the independence of students in learning while still being guided by the vision, mission, and educational goals that have been formulated. This study aims to determine the effect of the principal's managerial ability and teacher performance on the learning independence of students in the implementation of PTMT during the Covid-19 pandemic in MTs. Negeri 2 Kediri either simultaneously and also partially. The instrument used is a questionnaire which related to the managerial ability of the principal, teacher performance, and student learning independence. The instrument was analyzed using the SPSS application to find the relationship between variables related to data quality tests, prerequisite tests for linear regression analysis, and analysis of research hypothesis testing. The results stated that there was a significant simultaneous and partially effect between the managerial ability of the principal, and the teacher's performance on the learning independence of students in the implementation of PTMT pandemic at MTs. Negeri 2 Kediri.